2021
DOI: 10.1002/pmic.202000091
|View full text |Cite
|
Sign up to set email alerts
|

Membrane to cytosol redistribution of αII‐spectrin drives extracellular vesicle biogenesis in malignant breast cells

Abstract: Spectrin is a ubiquitous cytoskeletal protein that provides structural stability and supports membrane integrity. In erythrocytes, spectrin proteolysis leads to the biogenesis of plasma membrane extracellular vesicles (EVs). However, its role in non-erythroid or cancer-derived plasma membrane EVs biogenesis is unknown. This study aims to examine the role of αII-spectrin in malignant and non-malignant plasma membrane vesiculation. We developed a custom, automated cell segmentation plugin for the image processor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The relationship between membrane and cytoskeleton provides structural stability and one of the proteins involved in this stability is Spectrin. A reduction of Spectrin may be an indicator of cells with a higher propensity to vesiculate ( Taylor et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between membrane and cytoskeleton provides structural stability and one of the proteins involved in this stability is Spectrin. A reduction of Spectrin may be an indicator of cells with a higher propensity to vesiculate ( Taylor et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al showed the cell-permeable methyl ester derivative of the negatively charged cathepsin B inhibitor CA074ME reduces α-spectrin cleavage, similar to the effect of calpain inhibition [27]. Moreover, Taylor et al showed proteolysis of spectrin in erythrocytes results in the biogenesis of extracellular vesicles from the plasma membrane [28].…”
Section: Discussionmentioning
confidence: 97%